2010
DOI: 10.1111/j.1467-937x.2010.00610.x
|View full text |Cite
|
Sign up to set email alerts
|

How Important Is Human Capital? A Quantitative Theory Assessment of World Income Inequality

Abstract: We build a model of heterogeneous individuals—who make investments in schooling quantity and quality—to quantify the importance of differences in human capital vs. total factor productivity (TFP) in explaining the variation in per capita income across countries. The production of human capital requires expenditures and time inputs; the relative importance of these inputs determines the predictions of the theory for inequality both within and across countries. We discipline our quantitative assessment with a ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
129
0
6

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 186 publications
(147 citation statements)
references
References 25 publications
(63 reference statements)
12
129
0
6
Order By: Relevance
“…As shown by Engelbrecht (1997), general human capital affects Total Factor Productivity (TFP) as a factor of production, and as a vehicle for international knowledge transfer associated with productivity catch-up amongst economies in the Organization for Economic Corporation and Development (OECD). Erosa, Koreshkova, and Restuccia (2007) have also found that human capital accumulation strongly amplifies TFP differences across countries.…”
Section: Development and Growthmentioning
confidence: 99%
“…As shown by Engelbrecht (1997), general human capital affects Total Factor Productivity (TFP) as a factor of production, and as a vehicle for international knowledge transfer associated with productivity catch-up amongst economies in the Organization for Economic Corporation and Development (OECD). Erosa, Koreshkova, and Restuccia (2007) have also found that human capital accumulation strongly amplifies TFP differences across countries.…”
Section: Development and Growthmentioning
confidence: 99%
“…Howitt (2000) and Klenow and Rodriguez-Clare (2005) consider the accumulation of ideas, another produced factor. More recently, Manuelli and Seshadri (2005) and Erosa, Koreshkova and Restuccia (2010) have resurrected the human capital story in a more sophisticated fashion. similar to the original multi-sector business cycle model of Long and Plosser (1983).…”
Section: Input-output Economicsmentioning
confidence: 99%
“…Thus, most of the human capital effect would accrue to the quality of schooling which obviously differs from country to country (e.g. Erosa et al 2010).…”
Section: Impact Of Education On Human Capital and Migrationmentioning
confidence: 99%